Myanmar-based Khamti Shan Orthography - Douglas Inglis (Journal of the Southeast Asian Linguistics Society, 2017)
Khamti Shan, a Tai language spoken in Kachin State, Myanmar, is a northern dialect of Shan spoken in Shan State. Shan and Khamti Shan have adapted the Myanmar (Burmese) writing system for their own use. The Khamti Shan orthography was revised in 2006, fully integrated with current literacy applications and adapting a portion of the Myanmar Unicode set of characters along with an extended set of characters specific to Shan. Khamti Shan in Myanmar differs from the Northeast India variety (Tai Khamti) by distinguishing a palatal nasal and a rhotic. Described are the Khamti Shan phoneme-grapheme correspondences, engendering the segmental, suprasegmental and syllabic features of the orthography, along with a Latin-based transliteration guide for glossing of data. A transliterated and glossed text sample is found in the appendix.